Morphological Identification of Benthic Diatoms from Coral Reef Ecosystems of Bawean Island, East Jawa, Indonesia - Oktiyas Muzaky Luthfi; Yenny Risjani; Rendha Agustina Ramawati; Andrzej Witkowski (Journal of Multidisciplinary Applied Natural Science, 2026)
Small-sized benthic diatoms are frequently underrepresented in floristic surveys of coral reef ecosystems due to their inconspicuous morphology under light microscopy (LM). In this study, several benthic diatom strains were isolated into monoculture from coral reef substrates (sand, dead coral fragments, macroalgae, and surrounding seawater) collected at Bawean Island, East Java, Indonesia. The isolates were examined using LM and scanning electron microscopy (SEM) to clarify diagnostic morphological characters that are difficult to resolve with LM alone. Five taxa were documented: Psammodictyon sp., Halamphora cf. oceanica, Halamphora yundangensis, Halamphora sp., and Nitzschia arauriae. SEM observations revealed critical ultrastructural features, including raphe configuration, fibula structure, striae architecture, conopeum development, and internal valve morphology, which enabled more precise taxonomic evaluation and comparison with morphologically similar taxa. This work does not represent a comprehensive floristic inventory of reef-associated diatoms, but rather provides detailed SEM-guided morphological documentation of small (<20 µm), character-poor benthic taxa obtained in culture. These findings contribute taxonomic reference data for Indonesian marine diatoms and establish a morphological baseline for future integrative studies combining ultrastructural and molecular approaches.